Foreign Direct Investment (FDI) dan Efisiensi Energi Pada Industri Manufaktur di Indonesia - Ramdhan, Ilham; A Panennungi, Maddaremmeng (UI Scholars Hub, 2019)
This study aimed to analyse the relationship between FDI firms with energy intensity in Indonesian manufacturing industry and its sub-sector. The data used are from the Manufacturing Industry Survey obtained from the Central Statistiks Agency (BPS) with observation period 2007-2015. The model in this study were estimated used the fixed effect estimation method. Estimation results from the model showed FDI firms tend to have a negatifly correlated to the energy intensity that mean there is a decrease in energy intensity which indicates energy efficiency. In the industrial sub-sector FDI firms show varying correlation with the energy intensities. in additional, sub-sector with high energy intensif showed the non-metal excavation industry sector had a negatifly correlation and significant results on energy intensity, However, the base metals sector showed significant positive results that might occur due to the engineering effect of this industrial sector which was so low that there was no decrease in energy intensity Keywords: Energy intensity, Foreign Direct Investment (FDI), Manufacturing industry, Indonesia